Effects of Cross Cultural factors on Knowledge management of Kenya Homegrown Multinationals Operating in East Africa - Nzioki, Susan; Nyambagera, Stephen N.; Wawire, Nelson H. (The International Journal Of Business & Management, 2015)
The economic integration of the five East Africa regional countries has created unprecedented opportunities and new challenges. Kenya homegrown multinational firms have taken advantage of these opportunities by expanding their businesses in the region. However, cross-cultural diversity factors are affecting Strategic Human Resources Management activities in business management. This study sought to investigate the influence of cross-cultural diversity factors on Knowledge Management from a Strategic Human Resource Management perspective of Kenya homegrown multinational firm. From the sampled 17 selected companies a total of 284 managers were sampled from each category of companies as the respondents. The study showed that the main cross-cultural diversity factors namely differences in education system, language difference, business ethics and HRT culture influenced knowledge management in the East Africa Common Market. Based on these findings, recommendations were made, first was the need of harmonization of values in education systems of East Africa Community. Second, was to have a common official language that will enable easy coordination of business transactions, third was the harmonization of legal systems that promote positive values in business ethics. Fourthly, was the provision of human resource technology infrastructure that gives effective and efficient facilitation of strategic human resource management in the region? Lastly, Model proposal of Strategic Human Resource Management and knowledge manage was recommended.
Keywords: Knowledge management; Cross cultural diversity; East Africa common market; Kenya; Harmonization